A defect-induced broadband photodetector based on WS2/pyramid Si 2D/3D mixed-dimensional heterojunction with a light confinement effect. Issue 31 (29th July 2021) - Wu, Di; Guo, Chenguang; Wang, Zhaoyang; Ren, Xiaoyan; Tian, Yongzhi; Shi, Zhifeng; Lin, Pei; Tian, Yongtao; Chen, Yongsheng; Li, Xinjian
Abstract : A WS2 /pyramid Si 2D/3D mixed-dimensional vdW heterojunction device shows a broadband response spectrum up to 3.0 μm with high performance due to the strong light confinement effect of the pyramid Si and defect-induced narrowed bandgap of the WS2 film. Abstract : Broadband photodetection is of vital importance for both civil and technological applications. The widespread use of commercial photodiodes based on traditional semiconductors ( e.g. GaN, Si, and InGaAs) is limited to the relatively narrow response range. In this work, we have demonstrated a self-driven and broadband photodetector based on WS2 /pyramid Si 2D/3D mixed-dimensional van der Waals (vdW) heterojunction, which is assembled by directly transferring 2D WS2 film on 3D pyramid Si. Thanks to the enhanced light absorption with the pyramid Si structure, the defect-induced narrowed bandgap of the WS2 film, and high-quality vdW heterojunction, impressive device performances in terms of a large responsivity of 290 mA W −1, a high specific detectivity of up to 2.6 × 10 14 Jones and an ultrabroad response spectrum ranging from 265 nm to 3.0 μm are achieved at zero bias. Importantly, the photodetector can function as an infrared imaging cell with a high spatial resolution. The totality of these excellent features confirms that the demonstrated WS2 /pyramid Si 2D/3D mixed-dimensional vdW heterojunction device may hold great promise for applications in high-performance broadband infrared photodetection and imaging.